Vertical transmission of Severe Acute Respiratory Syndrome Coronavirus 2: A scoping review - Tolu, Lemi Belay (PLoS One, 2021)
INTRODUCTION: The evidence for vertical transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is not well established. Therefore, the objective of this review is to summarize emerging evidence on the vertical transmission of Severe Acute Respiratory Syndrome Coronavirus 2. METHODS: We conducted a systematic search in PubMed, CINAHL, Web of Science, SCOPUS, and CENTRAL. Likewise, a search for preprint publications was conducted using MedRxiv and Research Square. Studies that addressed vertical transmission of SARS-CoV-2 (concept) among pregnant women infected by Covid-19 (population) in any setting (community, hospital, or home) in any country or context were considered for inclusion. Any types of studies or reports published between December 2019 and September 2020 addressing the effects of SARS-CoV-2 on pregnant women and their newborn babies were included. Studies were screened for eligibility against the inclusion criteria for the review by two reviewers. RESULTS: We identified 51 studies reporting 336 newborns screened for COVID-19. From the 336 newborns screened for COVID-19, only 15 (4.4%) were positive for throat swab RT-PCR. All neonates with positive throat swab RT-PCR were delivered by cesarean section. Among neonates with throat swab SARS-CoV-2 positive only five (33.3%) had concomitant placenta, amniotic fluid, and cord blood samples tested, of which only one amniotic fluid sample is positive for RT PCR. Five neonates had elevated IgG and IgM but without intrauterine tissue tested. Four neonates had chest imaging suggestive of COVID-19 pneumonia. CONCLUSION: Currently there is not enough evidence on vertical virologic transmission of COVID-19 infection during the third trimester of pregnancy. Additionally, there is no evidence to support cesarean delivery, abstaining from breast feeding nor mother and infant separation. Further research involving an adequate sample size of breast milk, placenta, amniotic fluid, and cord blood to ascertain the possibility of vertical transmission and breast milk transfer is needed.